PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN PT. PANCA MULTI HARAPAN SEKTOR LOGAS RIAU ANDALAN PULP AND PAPER (RAPP) - Nurhayana, Nurhayana (Sekolah Tinggi Ilmu Ekonomi Riau, 2016)
The research purpose to know the effect of transformational leadership based on performance. The data were collected by giving questionaires to 44 employees by using slovin based on sample random sampling method. The research used qualitative and quantitative. The population of the research was the 144 employees of PT. Panca Mulya Harapan Sektor Logas Riau Andalan Pulp and Paper (RAPP). There were 44 respondents by using sample random sampling. Analysis model used by simple regration linear. The research prove that transformational leadership had positive impact and significanct influence of employees PT. Panca Mulya Harapan Sektor Logas Riau Andalan Pulp and Paper (RAPP)